Degree of phase transformations in the conditions of polythermal synthesis of SrBaFeMoO6–δ. (April 2020) - Kalanda, Nikolay; Yarmolich, Marta; Kutuzau, Maksim; Gurskii, Alexander; Soares, Maria do Rosário Teixeira; Andrulevičius, Mindaugas; Abakevičienė, Brigita; Tamulevičius, Sigitas
Abstract: The sequence of phase transformations during the crystallization of SrBaFeMoO6–δ by the solid-phase technique from a stoichiometric mixture of simple oxides SrCO3 + BaCO3 + 0.5Fe2 O3  + MoO3 was studied. It has been established that the synthesis of barium – strontium ferromolybdate proceeds through a series of sequential - parallel stages. It was found that to minimize the effect of intermediate reaction products, it is necessary to use combined synthesis modes. As a result of using combined synthesis modes for annealing for 20 h and T = 1443 K in vacuum of 10 −5 Torr at the pressure of residual oxygen gas 10 −8  Pa, it was possible to obtain a single-phase barium – strontium ferromolybdate compound with superstructural ordering of iron and molybdenum cations. Highlights: It has been established that the synthesis of SrBaFeMoO6–δ proceeds through a series of sequential - parallel stages. The gas medium is important in order to control oxygen deficiency for the Fe/Mo cations superstructural ordering formation. Single-phase SrBaFeMoO6–δ can be obtained in a vacuum of 10 − 5 Torr at a pressure of residual gaseous oxygen of 10 − 8 Pa. In order to minimize the effect of intermediate reaction products, it is necessary to use the combined synthesis modes. Using combined mode synthesis yielded single-phase SrBaFeMoO6–δ with Fe/Mo cations superstructural ordering.